IL-7 promotes the formation of DNA double strand breaks and DNA repair in murine pro-B cells - Lamolinara, Alessia; Di Lisio, Chiara; Hixon, Julie A.; Simeone, Pasquale; De Cola, Antonella; Falco, Maria D.; Meyer, Thomas J.; Ferrone, Alessio; Genovesi, Domenico; Lanuti, Paola; Li, Wenqing; De Laurenzi, Vincenzo; et al. (Frontiers in Immunology, 2025)
In pro-B cells, VDJ recombination at the immunoglobulin heavy chain locus is impaired. B cell progenitor recombination implies the formation of DNA double strand breaks (DSBs) by the RAG recombinase, which are subsequently repaired by specific mechanisms. We cultured primary murine pro-B cells with IL-7 to evaluate H2AX histone phosphorylation, a well-established marker of DSB formation (γ-H2AX foci) and the expression of proteins involved in DNA repair. Our results indicated that IL-7 upregulated the expression of several molecules involved in homologous recombination, the most accurate DSB repair mechanism. Quantitative analyses of γ-H2AX foci revealed that IL-7 significantly increased DSB formation in a time-dependent manner. Furthermore, γ-H2AX expression was altered in RAG2-deficient pro-B cells and absent in RAG1-deficient pro-B cells treated with IL-7, demonstrating the requirement of both RAG1 and RAG2 recombinase subunits. CD43 expression inversely correlates with the degree of cell differentiation and its level is often evaluated to assess the B lymphoid developmental stage. We observed that IL-7 upregulated CD43 expression and the percentage of large CD43/γ-H2AX double-positive cells, suggesting an effect on less differentiated, immature cells. Notably, we also found that IL-7 increased radiation-induced DSBs, while simultaneously supporting cell survival. This study uncovers novel effects of IL-7 on B cell differentiation, DSB formation, and DNA repair. It is well established that IL-7 promotes the proliferation and survival of acute lymphoblastic leukemia (ALL) cells. Our data suggest that drugs targeting IL-7 could improve ALL therapeutic protocols.